New Insight into Dearomatization and Decarbonylation of Antitubercular 4H‐Benzo[e][1, 3]thiazinones: Stable 5H‐ and 7H‐Benzo[e][1, 3]thiazines. (15th February 2022) - Richter, Adrian; Seidel, Rüdiger W.; Graf, Jürgen; Goddard, Richard; Lehmann, Christoph; Schlegel, Tom; Khater, Nour; Imming, Peter
Abstract: 8‐Nitro‐4 H ‐benzo[ e ][1, 3]thiazinones (BTZs) are potent in vitro antimycobacterial agents. New chemical transformations, viz . dearomatization and decarbonylation, of two BTZs and their influence on the compounds' antimycobacterial properties are described. Reactions of 8‐nitro‐2‐(piperidin‐1‐yl)‐6‐(trifluoromethyl)‐4 H ‐benzo[ e ][1, 3]thiazin‐4‐one and the clinical drug candidate BTZ043 with the Grignard reagent CH3 MgBr afford the corresponding dearomatized stable 4, 5‐dimethyl‐5 H ‐ and 4, 7‐dimethyl‐7 H ‐benzo[ e ][1, 3]thiazines. These methine compounds are structurally characterized by X‐ray crystallography for the first time. Reduction of the BTZ carbonyl group, leading to the corresponding markedly non‐planar 4 H ‐benzo[e][1, 3]thiazine systems, is achieved using the reducing agent (CH3 )2 S ⋅ BH3 . Double methylation with dearomatization and decarbonylation renders the two BTZs studied inactive against Mycobacterium tuberculosis and Mycobacterium smegmatis, as proven by in vitro growth inhibition assays. Abstract : The importance of carbonyl : Reactions of the antituberculosis drug candidate BTZ043 and its 2‐piperidinyl derivative with the Grignard reagent CH3 MgBr afforded the dearomatized stable 4, 5‐dimethyl‐5 H ‐ and 4, 7‐dimethyl‐7 H ‐benzo[ e ][1, 3]thiazines, which were structurally characterized by X‐ray crystallography. Reduction of the BTZ carbonyl group was achieved with the reducing agent (CH3 )2 S ⋅ BH3 . Both chemical transformations resulted in loss of antimycobacterial activity.